2015
DOI: 10.1016/j.msea.2015.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the hot flow behavior of a Fe–22Mn–0.41C–1.6Al–1.4Si TWIP steel microalloyed with Ti, V and Nb

Abstract: Cite this article as: I. Mejía, F. Reyes-Calderón and J.M. Cabrera, Modeling the hot flow behavior of a Fe-22Mn-0.41 C-1.6Al-1.4Si TWIP steel microalloyed with Ti, V and Nb, Materials Science & Engineering A, http://dx. AbstractThe present research work analyses the influence of Ti, V and Nb microalloying elements on the hot flow behavior of a high-Mn TWIP (Twinning Induced Plasticity) steel. For this purpose, flow curves were obtained by uniaxial hot compression tests performed at four strain rates (10 -1 , 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 63 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…In contrast, different research works refer to the excessive equiaxial grain growth in the HAZ of TWIP steels, using different fusion welding processes such as laser and resistance spot welding . It is worth highlighting that although the HAZ of TWIP‐Ti steel showed grain growth, this growth was not excessive, which can be associated to the low heat input used in the semiautomatic GTAW process and the grain growth inhibition effect of Ti as a microalloying element …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, different research works refer to the excessive equiaxial grain growth in the HAZ of TWIP steels, using different fusion welding processes such as laser and resistance spot welding . It is worth highlighting that although the HAZ of TWIP‐Ti steel showed grain growth, this growth was not excessive, which can be associated to the low heat input used in the semiautomatic GTAW process and the grain growth inhibition effect of Ti as a microalloying element …”
Section: Resultsmentioning
confidence: 98%
“…It is well known that Ti allows the formation of precipitates at high temperatures, which can inhibit grain growth . Mejia et al showed the effect of Ti as a grain refiner in TWIP steels, reporting that a TWIP steel microalloyed with Ti exhibited a grain size of 63 ± 32 μm, whereas the TWIP steel without a microalloying element showed a grain size of 104 ± 23 μm after austenitization at high temperatures. Most probably the present annealing temperature was not enough to completely dissolve the TiN particles, and therefore some abnormal grain growth took place.…”
Section: Resultsmentioning
confidence: 99%
“…where U and Ω are the hardening and softening parameters, respectively. Both parameters are assumed to be independent of the applied strain [30]. Thus, the dislocation density can be obtained by integration of Eq.…”
Section: Modeling the Mechanical Behaviormentioning
confidence: 99%
“…A large number of studies have shown that physical models are widely used to describe the complex flow behaviors of metals, such as Johnson-Cook type [5,6], Arrhenius type [7,8], Bergstrom type [9], Kolmogorov-Johnson-Mehl-Avrami type [10], etc. The physical model is based on a set of parameters that can be expressed as a function of forming temperature, strain, and strain rate.…”
Section: Introductionmentioning
confidence: 99%